Managerial features and outcome in neonatal intensive care units: results from a cluster analysis - Simone Fanelli; Roberto Bellù; Antonello Zangrandi; Luigi Gagliardi; Rinaldo Zanini (BMC, 2020)
Abstract Background Healthcare organisations differ in performance even if they are located in the same country or region. Suitable managerial practices and organisational processes can lead to better health outcomes. As a result, hospitals are constantly looking for managerial arrangements that can improve outcomes and keep costs down. This study aims to identify different managerial models in neonatal intensive care units (NICUs) and their impact on a large number of outcomes. Methods The research was conducted in Italy, within the SONAR project. SONAR's aim was to identify the characteristics of NICUs, monitor outcomes and promote best practices. This study includes 51 of the 63 NICUs that took part in the SONAR project. Questionnaires on the activities and managerial features were administered to doctors and nurses working in NICUs. A total of 643 questionnaires were analysed from doctors and a total of 1601 from nurses. A cluster analysis was performed to identify managerial models of NICUs. Results Three managerial models emerged from cluster analysis: traditional, collaborative and individualistic. In the "traditional" model the doctor is above the nurse in the hierarchy, and the nurse therefore has exclusively operational autonomy. The "collaborative" model has as key elements professional specialisation and functional coordination. The "individualistic" model considers only individual professional skills and does not concern the organisational conditions necessary to generate organisational effectiveness. The results also showed that there is an association between managerial model and neonatal outcomes. The collaborative model shows best results in almost all outcomes considered, and the traditional model has the worst. The individualistic model is in the middle, although its values are very close to those of traditional model. Conclusions Health management needs to assess NICU strategically in order to develop models to improve outcomes. This study provides insights for management useful for designing managerial characteristics of NICUs in order to achieve better results. NICUs characterised by a collaborative model in fact show better neonatal outcomes.